2012
DOI: 10.1111/j.1467-9515.2012.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Black‐market Medicine and Public Opinion Towards the Welfare State: Evidence from Israel

Abstract: Based on a survey and interviews, this article presents and analyses Israeli public opinion toward black-market medicine (BMM) and the welfare state. In addition to providing quantitative and qualitative evidence of the existence of under-the-table payments in Israel, we suggest various insights into this phenomenon. While most citizens admit that they would consider making under-the-table payments in order to receive preferential medical treatment, when the questions mention words such as 'illegal' or 'bribe'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Therefore, decision-makers should not underestimate this phenomenon. This point is especially important given that these numbers are in line with other studies (Cohen et al, 2012;Filc and Cohen, 2015;Cohen and Filc, 2017) and accord with the fact that the alternative provision of health care services is not a new phenomenon in Israel (Shvarts et al, 1999). Hence, 84% of Israelis believe that without a direct connection to the centers of power in the HMOs and hospitals, they will not be able to obtain appropriate medical treatment in case of serious illness (Brammli-Greenberg et al, 2019).…”
Section: Israeli Citizens' Attitudes and The Health Care Systemsupporting
confidence: 64%
“…Therefore, decision-makers should not underestimate this phenomenon. This point is especially important given that these numbers are in line with other studies (Cohen et al, 2012;Filc and Cohen, 2015;Cohen and Filc, 2017) and accord with the fact that the alternative provision of health care services is not a new phenomenon in Israel (Shvarts et al, 1999). Hence, 84% of Israelis believe that without a direct connection to the centers of power in the HMOs and hospitals, they will not be able to obtain appropriate medical treatment in case of serious illness (Brammli-Greenberg et al, 2019).…”
Section: Israeli Citizens' Attitudes and The Health Care Systemsupporting
confidence: 64%
“…Using a survey sample of 507 adults from the Israeli‐Jewish population, Cohen et al . () found that there is a basic willingness among Israeli citizens to adopt strategies associated with informal payments for health care and claim that these findings are also supported by interviews in which most participants note the existence of such behavior in Israeli society and even claim that it tends to be normative. However, their study investigated only citizens' attitudes and willingness to use informal payments for health care, not their behavior.…”
Section: The Israeli Health Care Systemmentioning
confidence: 88%
“…The term “black market medicine” refers to a variety of illegal and semi‐legal actions that individuals take in order to obtain healthcare services for themselves. Such actions include direct payments to physicians in order to improve one's position on the waiting list (especially for surgeries), payments to physicians in order to guarantee personal treatment, donations to the research funds of the hospital department where the patient is being treated in order to receive better treatment, payments for treatment that is supposed to be given free of charge in the framework of the regular healthcare insurance in the hopes of improved care and physicians' use of instruments and public buildings without permission in order to treat their private patients (Cohen et al ., ). These payments are corrupting and considered part of the shadow economy (Schneider, ; Schneider and Buehn, ).…”
Section: Informal Payments For Health Carementioning
confidence: 97%
“…This approach allows free market forces freedom of operation and reduces the state's responsibility for its citizens (Doron ). Nevertheless, studies demonstrate that in general the public favours an inclusive welfare state and generous social policy (Shalev ; Cohen et al ), and justifies state intervention and public investment in social services, particularly for those who are considered deserving (Cohen et al ).…”
Section: Context: Israeli Social Workers and Urban Renewal Projectsmentioning
confidence: 99%